The Impact of Nontariff Trade Policy of European Union Crude Palm Oil Import on Indonesia, Malaysia, and the Rest of the World Economy: An Analysis in GTAP Framework - Rozy A. Pratama; Tri Widodo (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2020)
Indonesia and Malaysia are the largest producers and exporters of palm oil in the world vegetable oil market. Palm oil and its derivative products are the highest contributors to foreign exchange in 2018. This study aims to analyze the impact of the European Union import non-tariff trade policies on the Indonesian and Malaysian economies The analysis uses the Computable General Equilibrium (CGE) model of world trade on the Global Trade Analysis Project (GTAP) program. The results of this study found that the non-tariff import policy by the European Union had a negative impact on the economies of Indonesia and Malaysia. Moreover, the policy also has a negative impact on countries in Southeast Asia and the European Union. This shows that the enactment of non-tariff import trade policies for Indonesian and Malaysian palm oil products has a global impact.